A narrative review of the intermediate category of the antimicrobial susceptibility test: relation with dosing and possible impact on antimicrobial stewardship. (30th December 2022) - Yusuf, Erlangga; Zeitlinger, Markus; Meylan, Sylvain
Abstract: The interpretation of 'susceptible (S)' or 'resistant (R)' results of antimicrobial susceptibility testing is easily understood, but the interpretation of the 'intermediate (I)' category can be confusing. This review critically discusses how this categorization (clinical breakpoints) comes into being with the emphasis on the use of pharmacokinetics and pharmacodynamic data. It discusses the differences between the 'I' according to the CLSI and the EUCAST. This review also discusses the recent EUCAST change of the 'I' definition, and the impact of this change from laboratory and clinical points of view.